Effect of Hemodialysis on Intraocular Pressure (IOP) and Ocular Perfusion Pressure (OPP): Hemodialysis Effects on IOP and OPP - Obaidullah, Muhammad; Idrees, Maria; Majeed, Safia; Majeed, Khadija; Asadullah, Muhammad; Majeed, Javaria; Ahmed, Maria (Pakistan Journal of Health Sciences, 2025)
Hemodialysis is a routine procedure in patients on renal replacement therapy. It carries risk of intraocular pressure and ocular perfusion pressure derangement. With proper monitoring of IOP and blood pressure, visual impairment can be minimized. Objective: To study the effect of hemodialysis on intraocular pressure (IOP) and ocular perfusion pressure (OPP). Methods: Cross sectional observational study after getting ethical approval was carried out in a Tertiary Care Hospital Rawalpindi from Aug 2021 to Apr 2022. Sixty patients with CKD on HD were included. A pneumotonometer was used to measure IOP twice at every time point. IOP was measured Pre-HD, during HD, and Post-HD. After measuring IOP and BP the value of OPP, MAP, SOPP and DOPP were calculated. Statistical analysis was done using SPSS version 21.0. Results: The value of IOP at pre-HD was 18.82 ± 0.57, during HD was 20.73 ± 0.55 and post-HD was 21.55 ± 0.60. Similarly, the value of MAP at pre-HD was 93.48 ± 4.26, during HD was 88.25 ± 4.71 and post-HD was 84.63 ± 5.20. The value of OPP at pre-HD was 74.70 ± 4.23, during HD was 67.50 ± 4.80 and post-HD was 63.13 ± 5.19. Pre-HD to post-HD the value of IOP increased significantly to 2.73 mmHg, MAP decreased significantly to -8.85 mmHg and OPP decreased significantly to -11.57 mmHg. Conclusions: During HD, there is a significant rise in IOP and reduction in OPP, both of which enhance the risk of glaucoma progression and development. Even when IOP is effectively managed, clinicians must evaluate HD history in patients with glaucoma progression.